High-frequency hearing loss and middle ear involvement in rheumatoid arthritis - Öztürk, A; Yalçin, I; Kaygusuz, I; Sahin, S; Gök, U; Karlidag, T; Ardiçoglu, Ö (W B Saunders Co-Elsevier Inc, 2004)
Purpose: We aimed to evaluate the possible changes in the middle ears of patients with rheumatoid arthritis (RA) and to measure their hearing functions by eleven different test frequencies including standard and high frequencies. Materials and Methods: The study group was comprised of 74 patients with RA. The control group was comprised of 45 healthy subjects. We performed speech test, tympanometry, acoustic reflex test, and standard and high-frequency pure tone audiometric tests in the study and the control groups. Results: It was observed that significant increases in the thresholds of pure tones in all test frequencies for the study group versus the controls (P <.0001). In terms of the duration of the disease, hearing loss of the patients with disease duration of 1 to 5 years was higher than that of the controls and exceeded beyond the level of 20 dB especially in high frequencies starting from 10,000 Hz. In patients with disease duration of 6 to 10 years, the beginning point for hearing loss was 4,000 Hz. The patients with disease duration of 11 to 15 years and of above 16 years had high hearing thresholds in all frequencies. We found normal pressure in the middle ears of the study and the control groups. Conclusion: Sensorineural type hearing loss developed in patients with RA especially in high frequencies. We also determined a diminished compliance in the middle ears of those patients, but this was not in a level of a conducting type hearing loss. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: Hydroxychloroquine Ototoxicity